PENGARUH TIME BUDGET PRESSURE DAN INTEGRITAS TERHADAP KUALITAS AUDIT DENGAN DYSFUNCTIONAL AUDIT BEHAVIOUR SEBAGAI VARIABEL INTERVENING - Nabila Tiara, NT (2020)
EFFECT OF TIME BUDGET PRESSURE AND INTEGRITY ON AUDIT QUALITY WITH DYSFUNCTIONAL AUDIT BEHAVIOUR AS INTERVENING VARIABLE By Nabila Tiara ABSTRACT The research is type of quantitative study with primary data that aims to examine the effect of Time Budget Pressure and Integrity variables on Audit Quality through Dysfunctional Audit Behaviour as an intervening variable. The sample in this research is 121 auditors working at The Jakarta Public Accountant Firm was selected using probability sampling and simple random sampling technieques.The analysis data used path analysis and operation by SmartPLS 3.0 software with significance level of 0,05 (5%). Present in this research use Dysfunctional Audit Behaviour as an intervening variabel. The reseach method is use the Structura; Equation Model (SEM). The result of this analysis are: (1) Time Budget Pressure has no significant effect on Audit Quality, (2) Integrity has a significant effect on Audit Quality, (3) Time Budget Pressure has a significant effect on Dysfunctional Audit behaviour, (4) Integrity has a significant effect on Dysfunctional Audit behaviour, (5) Dysfunctional Audit behaviour has no significant effect on Audit Quality, (6) Time Budget pressure has no significant effect on Audit Quality through Dysfunctional Audit Behaviour, (7) Integrity has no significant effect on Audit Quality through Dysfunctional Audit Behaviour. Keyword: Audit Quality, Time Budget Pressure, Integrity, Dysfunctional Audit Behaviour.